Endoscopic Pilonidal Sinus Treatment (EPSIT) Vs Total Excision with Primary Closure (EPC) for Pilonidal Sinus Disease in Combined Military Hospital Rawalpindi - Muazzam, Muhammad Ali; Hussain, Syed Mukarram; Quraishi, Muhammad Tanvir Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare endoscopic pilonidal sinus treatment (EPSIT) vs total excision with primary closure (EPC) for pilonidal sinus disease in Combined Military Hospital Rawalpindi regarding intra and post-operative outcomes.Study Design: Comparative cross-sectional.Place and Duration of Study: Department of Surgery, Combined Military Hospital Rawalpindi, from Sep 2017 to Aug 2018.Methodology: A total of 94 patients, all male patients were included. All 94 have primary pilonidal sinus; Patient were randomized in a double-blind study to undergo EPSiT or EPC by non-probability, consecutive sampling into two equal groups.Results: The mean ± age SD of patients was 28 years ± 2.6 years. All patients completed the follow-up. All 94 patients divided equally for EPSiT and EPC. The patients completed the follow-up. All 94 patients divided equally for EPSiT and EPC. Surgery duration of EPSiT with a median duration of 34.5 minutes (IQR 30-39) and EPC 40.5 minutes (IQR 35-46); The median hospital stay was 8.5 hours (IQR 4-14) in EPSIT and 21.5 hours (IQR 15-28) in EPC. Complete wound healing in EPSiT was 93.6% and EPC was 81%. Wound complication rate was lower for EPSiT 3 (6.3%) and 8 (17%) or EPC (p-value 0.108). One case of wound dehiscence reported in EPC. Recurrence occurred in EPSiT was 3(6.3%) and EPC 9(19.1%).Conclusions: In our experience, EPSiT was viable as EPC in the treatment of pilonidal sinus.